The dual role of candida glabrata drug:H+ antiporter CgAqr1 (ORF CAGL0J09944g) in antifungal drug and acetic acid resistance - Costa, Catarina; Henriques, André S.; Pires, Carla; Nunes, Joana; Ohno, Michiyo; Chibana, Hiroji; Sá-Correia, Isabel; Teixeira, Miguel C. (Frontiers in Microbiology, 2013)
Opportunistic Candida species often have to cope with inhibitory concentrations of acetic acid, in the acidic environment of the vaginal mucosa. Given that the ability of these yeast species to tolerate stress induced by weak acids and antifungal drugs appears to be a key factor in their persistence and virulence, it is crucial to understand the underlying mechanisms. In this study, the drug:H+ antiporter CgAqr1 (ORF CAGL0J09944g), from Candida glabrata, was identified as a determinant of resistance to acetic acid, and also to the antifungal agents flucytosine and, less significantly, clotrimazole. These antifungals were found to act synergistically with acetic acid against this pathogen. The action of CgAqr1 in this phenomenon was analyzed. Using a green fluorescent protein fusion, CgAqr1 was found to localize to the plasma membrane and to membrane vesicles when expressed in C. glabrata or, heterologously, in Saccharomyces cerevisiae. Given its ability to complement the susceptibility phenotype of its S. cerevisiae homolog, ScAqr1, CgAqr1 was proposed to play a similar role in mediating the extrusion of chemical compounds. Significantly, the expression of this gene was found to reduce the intracellular accumulation of 3H-flucytosine and, to a moderate extent, of 3H-clotrimazole, consistent with a direct role in antifungal drug efflux. Interestingly, no effect of CgAQR1 deletion could be found on the intracellular accumulation of 14C-acetic acid, suggesting that its role in acetic acid resistance may be indirect, presumably through the transport of a still unidentified physiological substrate. Although neither of the tested chemicals induces changes in CgAQR1 expression, pre-exposure to flucytosine or clotrimazole was found to make C. glabrata cells more sensitive to acetic acid stress. Results from this study show that CgAqr1 is an antifungal drug resistance determinant and raise the hypothesis that it may play a role in C. glabrata persistent colonization and multidrug resistance.